STRATEGI PENGEMBANGAN KOPERASI DALAM UPAYA MEMBANGUN KESEJAHTERAAN MASYARAKAT - Mujib Ikhsani, Mastur; Pradhipta Aryoko, Yudhistira (Derivatif : Jurnal Manajemen, 2019)
One of the big enough roles to contribute is the Micro, Small and Medium Enterprises (MSME) sector. The MSME sector is a sector that is quite strong in the Indonesian economy, a sector that is proven to be able to avoid the crisis that has struck the State of Indonesia several times. But in implementation, MSMEs have various problems caused by various factors. Several factors such as the difficulty of the community to spend MSMEs which are important in the activities of MSMEs. Capital is one that supports MSMEs in starting their businesses or developing their businesses. Therefore, in the implementation of MSMEs, the community also requires strong capital in order to survive the difficulties brought by MSMEs. alternative solutions that can be done by MSMEs are access to MSME capital by financial institutions such as cooperatives.                The purpose of this research is to study cooperative development strategies for the welfare of the community through MSMEs. Knowing the problems and solutions in cooperative development. This study uses a SWOT analysis to obtain cooperative development strategies for community welfare.                The results showed the Cooperative in Banyumas Regency had a very strategic position to support the development of winning strategies. Cooperatives in Banyumas Regency are located in quadratic I, which is meant in this position Cooperatives in Banyumas Regency are very supportive to develop an improvement strategy in order to get the company to compete with other business entities. Keyword: Cooperative, UMKM, Community Welfare, SWOT